Community Empowerment Through Biopore Creation as an Effort to Mitigate Flood and Organic Waste Management - Raka Singgih; Rafi Refliansyah Indra; Abdul Majid; Sidki Alihsan; Rafi Refliansyah; Ana Jainab; Reysa Adelia Sapitra; Arwa Suminta; Firman Firman; Asep Suryana; Dadang Wiranta (Siber Nusantara of Community Service Review, 2026)
The problem of flooding and organic waste management is still a major issue in residential areas with high levels of density and suboptimal drainage systems. Low soil permeability and lack of public awareness in managing waste worsen environmental conditions. This activity aims to increase community capacity in flood mitigation and organic waste management through the creation of empowerment-based biopore infiltration holes. The method used is Participatory Action Research (PAR) which actively involves the community in the planning, implementation, observation, and reflection stages. Data collection techniques are carried out through observation, interviews, documentation, and focus group discussions. The results of the activity show that this program is able to increase community understanding, skills, and participation in environmental management. The application of biopores has been proven to increase water infiltration, reduce inundation, and encourage the use of organic waste as compost. In addition, there has been a change in community behavior in sorting and managing waste independently. Although there are still obstacles in consistency and equal participation, in general this program is effective as a simple, economical, and sustainable solution. Thus, the biopore-based empowerment model has the potential to be replicated in community-based environmental management efforts.